1993
DOI: 10.1071/ea9930531
|View full text |Cite
|
Sign up to set email alerts
|

The performance of Brahman-Shorthorn and Sahiwal-Shorthorn cattle in the dry tropics of northern Queensland. 4. Postweaning growth and carcass traits

Abstract: Postweaning growth to slaughter at 42 months of age in males and to initial mating at 27 months of age in females was studied in 4 inter se mated Bos indicus crosses in a dry tropical environment. Six-monthly growth periods from weaning (at about 6 months of age) generally coincided with wet and dry seasons. The cattle represented were second and subsequent generations of 112 Brahman and 112 Sahiwal crosses and first backcross and later generations of 314 Brahman and 314 Sahiwal crosses, The Bos taurus compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Such interannual variability in production is common in the northern savannas of Australia (e.g. Fordyce et al 1993) and reflects the inherent variation in the amount and distribution of rainfall. The seasonal pattern of LWG observed within grazing years is also well documented (Gillard 1979;Fordyce et al 1993) and obviously reflects the marked seasonality of rainfall in the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interannual variability in production is common in the northern savannas of Australia (e.g. Fordyce et al 1993) and reflects the inherent variation in the amount and distribution of rainfall. The seasonal pattern of LWG observed within grazing years is also well documented (Gillard 1979;Fordyce et al 1993) and obviously reflects the marked seasonality of rainfall in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Fordyce et al 1993) and reflects the inherent variation in the amount and distribution of rainfall. The seasonal pattern of LWG observed within grazing years is also well documented (Gillard 1979;Fordyce et al 1993) and obviously reflects the marked seasonality of rainfall in the region. Despite this variability, there were consistent trends in relative animal performance driven largely by stocking rate.…”
Section: Discussionmentioning
confidence: 99%
“…The overall expression of growth is liveweight gain, which is a function of growth of the musculoskeletal system, along with growth of all other body systems. There are limited reports on the growth of beef heifers in the dry tropics of northern Queensland (Holroyd et al 1990;Fordyce et al 1993b;Barwick et al 2009). There are even fewer reports of skeletal measures and growth for tropically adapted cattle in northern Australia (Barwick et al 2009;Wolcott et al 2014) than there are of liveweight gain, and no specific reported studies on non-genetic interventions to manage heifer growth.…”
Section: Introductionmentioning
confidence: 99%